(1,3-benzothiazol-2-yl)[1-(2-chlorobenzyl)imidazolidin-2-ylidene]amine - Yildirim, Sema Ozturk; Akkurt, Mehmet; Danisman, Osman; Sekerci, Memet; Fun, H. -K. (Int Union Crystallography, 2006)
In the crystal structure of the title compound, C17H15ClN4S, the benzothiazole, imidazolidine and benzene rings are twisted relative to each other.
Keywords: 2-Arylamino-2-Imidazolines; Derivatives